2020
DOI: 10.4081/gh.2020.868
|View full text |Cite
|
Sign up to set email alerts
|

Employment of Mapping Technology in Antimicrobial Resistance Reporting in Saudi Arabia

Abstract: Although Antimicrobial Resistance (AMR) is a worldwide threat, local AMR databases do not exist. Unlike other health disasters, developing containment strategies for AMR cannot be started without a representative, local, updated AMR data. However, Geographical Information Systems (GIS) mapping technology is capable of visualizing AMR data integrated with geographical regions. Due to the absence of AMR databases in Saudi Arabia, we searched Medline and Embase databases from inception until May 28, 2018, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…However, Ohmura and his colleagues reported that a low-dose treatment regimen of TMP-SMX with <10 mg/kg/day for TMP was as well-tolerated and effective as high-dose therapy [ 26 ]. Similarly, Schild et al reported that the patients received an intermediate-dose TMP-SMX (TMP 10–15 mg/kg/day) but later on, 23% of patients switched to low-dose TMP-SMX due to various AEs and this regimen was deemed to be safe and effective in patients with various immune dysfunctions [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, Ohmura and his colleagues reported that a low-dose treatment regimen of TMP-SMX with <10 mg/kg/day for TMP was as well-tolerated and effective as high-dose therapy [ 26 ]. Similarly, Schild et al reported that the patients received an intermediate-dose TMP-SMX (TMP 10–15 mg/kg/day) but later on, 23% of patients switched to low-dose TMP-SMX due to various AEs and this regimen was deemed to be safe and effective in patients with various immune dysfunctions [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although highly recommended by the healthcare community, prophylactic drugs are included in the crucial immunosuppressive regimen, resulting in considerable economic burden for the immunocompromised patients [ 38 ]. Routine PCP prophylaxis is recommended for patients treated in hospitals where the prevalence of PCP is at least 3% to 5% among immunocompromised patients [ 12 , 39 , 40 ]. Moreover, the risk of PCP among transplant recipients is greater in 1–6 month post-transplantation period, during prolonged neutropenia, or in patients receiving steroids, antilymphocyte antibodies, or calcineurin inhibitors [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Hajj presents substantial logistic challenges for the protection of both non-residents and residents of KSA as well as the maintenance of local, national and international health security [ 17 , 30 ]. Infectious diseases including Zika virus diseases, extensive drug-resistant tuberculosis, (XDR TB), Middle East Respiratory Syndrome (MERS), seasonal influenza and severe acute respiratory syndrome coronavirus (SARS-CoV) have all surfaced in recent decades [ 31 , 32 , 33 , 34 , 35 ]. New policies by Saudi Ministry of Health have been implemented to try and reduce the transmission of infectious diseases during the Hajj.…”
Section: Introductionmentioning
confidence: 99%
“…Optimizing the dosing of antibiotics is crucially important due to the increasing rate of drug resistance, limited number of new antibiotics and high mortality associated with hospital-acquired infections especially with gram-negative bacteria ( Abdul-Aziz et al, 2020a , Abdul-Aziz et al, 2020b ). Several studies in Saudi Arabia have reported over the last 20 years an increased prevalence of multi-drug resistant gram-negative bacteria especially carbapenem-resistant gram-negative bacteria ( Al Johani et al, 2010 , Balkhy et al, 2012 , Yezli et al, 2014 , Al-Obeid et al, 2015 , Elabd et al, 2015 , Zowawi et al, 2015 , Zowawi, 2016 , Zowawi et al, 2018 , Alotaibi, 2019 , Alhifany et al, 2020 , Nasser et al, 2020 ). For example, the susceptibility of Acinetobacter baumannii to meropenem decreased from ∼70% in 2006 to ∼10% in 2012 ( Al-Obeid et al, 2015 ) .…”
Section: Introductionmentioning
confidence: 99%